Bitcoin, IPO, ETF and Crowdfunding - BHASKAR, Nirupama Devi (Institutional Knowledge at Singapore Management University, 2015)
We discuss the recent attempts at initial public offering (IPO) for Bitcoin entities on traditional exchanges and the emergence of alternative unregulated decentralized exchanges via blockchain technology in this chapter. The first part of this chapter considers, as case studies, the legal structure of the Digital CC IPO in Australia, the Winklevoss Bitcoin Trust as an exchange-traded fund in the United States. The second part explores the emerging use of cryptocurrencies for off-exchange crowdfunding efforts and potential of such technologies for automatic distributed exchanges. Finally, we discuss the possibility and risk involved in Initial Crowd Offering (IWO) using cryptocurrency as a universal fund raising currency.